EQUIVALENCE AND ADEQUACY IN LITERARY TRANSLATION: THEORETICAL PERSPECTIVES - Xolmurzayev , Oybek (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis investigates the theories of equivalence and adequacy in literary translation based on the concepts of Eugene Nida, Verner Koller, and Peter Newmark. The paper analyses various levels of equivalence — denotative, connotative, pragmatic, and formal — and examines their application in English-Uzbek literary translation practice. The findings shed light on the tensions between levels of equivalence and the key challenges translators face.